Moving with Whatcom Falls Park: A Score for Unsettling in Place - Marchinko, Elan (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2021)
In July 2020, I relocated from the territory of the Lenape in New York City, New York, to the ancestral homelands of the Coast Salish Peoples and the Lummi Nation and Nooksack Tribe, otherwise known as Bellingham, Washington. As a settler Canadian and "dependent" on my partner's US work visa, I wrestle with my precarious yet privileged footing here in the southern part of Turtle Island. As well, friends and family often ask me how I am "settling in." I deploy this very question as a provocation to ask, As a white settler, what does it mean to both responsibly unsettle oneself and "settle in" to a new home on stolen land? At the same time, due to the complexities of moving across the country during COVID-19, I feel unmoored and disconnected from my immediate surroundings. I am the most grounded when I am dancing. Working through the metatarsals of my feet, those bones that absorb shock and engender soft landings, is both a metaphor and a methodology for my practice-based research as a settler artist-scholar. Thus, through a piece that is part photo essay and part embodied reflection, I move with the land here on the west coast. With Whatcom Falls Park as my studio and soundscape, I will work through these questions and acknowledge the Coast Salish Peoples, the Lummi Nation, and the Nooksack Tribe, on whose land I currently move.